Управление программными лабораторными средствами в системе дистанционного обучения - Шеховцов, Б. Г.; Середенко, В. А. (My University, 2002)
With development of remote training there is a problem of management of all program operating time located on a server part of system. In given article one of variants of the decision of a problem of management is considered by the software developed on faculty of the COMPUTER
Keywords: дистанционне обучение; образование